What: does Ramon Llull mean when he says «[el resclús] se maravellà com podia esser que Déus no exoya la natura humana de Jesucrist, qui piegava per son poble la natura divina», (Fèlixo Llbre de meravelles, Ch. 105, «De la oració»)? - HUGHES, ROBERT DESMOND (Scripta)
The proto-novel Félix, o Llibre de meravelles contains many unsettling; «meravelles» or «wonders». One such consists in an observation made by a «recluse» --rather than by a professional theologian-- concerning the prayers of Christ and of Mary and the angels, etc., to the effect that their prayers have been unable to call forth any response from God. The efficacy of such prayers is thus brought into question, as is the readiness of God's mercy and grace. By contextualising such matters within medieval currents of Neoplatonism, particularly the doctrine of causality, I argue that Llull presents a causally conceived theorisation of the hypostatic union. I identify Biblical and medieval precedents for and contrasts with Llull's position on prayer and relate this latter to the sometimes fluid notions of orthodoxy as regards Christological matters among medieval writers, pausing to focus in particular on Llull's use of the soul-body analogy for the union of natures in Christ. I examine the apparent contradiction present in Llull's construal of the efficacy of Christ's prayer--in this context, implicitly conceived as a prayer of petition--and attempt to resolve this contradiction in a way which indicates clearly Ramon Llull's relation to orthodoxy at least during the period 1274-89.